Innovations in the Ethical Review of Health-Related Quality Improvement and Research: The Alberta Research Ethics Community Consensus Initiative (ARECCI) - Hagen, Brad (Longwoods Publishing, 2007)
The Alberta Research Ethics Community Consensus Initiative (ARECCI) is a unique Canadian initiative that addresses the ethical oversight of two main categories of health-related investigative projects: research and quality improvement (including quality assurance and program evaluation). ARECCI was formed as a result of discussions arising from health regions, health researchers and the Alberta Committee of Research Ethics Boards (REBs) Chairs, who all desired a clearer and more consistent approach to the ethical oversight of investigative health projects. The Alberta Heritage Foundation for Medical Research (AHFMR) established and supported ARECCI in 2003 in response to this need. ARECCI is unique in its ongoing efforts to bring together a wide-ranging group of stakeholders to develop consensus on a set of pragmatic recommendations and tools for the ethical review of research and quality improvement, and to get extensive consultation on those recommendations. This paper presents the ARECCI context and process, recommendations and tools produced by ARECCI and lessons learned from the ongoing ARECCI process.